Legal Protection of Consumers in Electronic Transactions: Challenges and Future Prospects - Nanda Dwi Rizkia; Wahab Aznul Hidaya; Diah Turis Kaemirawati; Rica Regina Novianty; Yenny Febrianty (Journal Equity of Law and Governance, 2024)
Examining how successfully consumer protection legislation in Indonesia have kept up with the evolution of digital technology and how well they have been applied to online transactions is the primary goal of this study. In this age of ubiquitous electronic transactions, the significance of consumer protection has never been greater, as this study shows. Analysis of statutes, regulations, and other relevant legal documents is part of the normative research literature review methodology. Included in the literature review are the following statutes and regulations: Law 8 of 1999, which deals with consumer protection; Government Regulation 71 of 2019, which deals with the implementation of electronic systems and transactions; and Regulation 5 of 2020, which deals with the implementation of private scope electronic systems, which is ministerial decree. While the current standards are thorough, there are still several challenges to putting them into practice, according to the report. Consumers' ignorance of their rights, ineffective dispute resolution processes, and lax law enforcement are all factors contributing to this problem. Furthermore, this study delves into the significance of enhancing consumer safety via education and bolstering monitoring, as well as the need of revising rules to account for ever-evolving technology advancements.